Nurses’ Caring Behaviors as Perceived by Patients and Nurses in a Surgical Service, Banglamung Hospital - Pahsuk, Anothai (Journal of Nursing and Public Health Research, 2021)
The objectives of this descriptive study were to develop a questionnaire for measuring nurses’caring behaviors as perceived by patients and nurses and to determine if nurses rated these behaviors differently than patients. There were 266 participants: 209 patients (78.6%) and 57 nurses (21.4%) from the inpatient surgical unit and an operating room. Data were collected between July 1 and August 31, 2019. The instruments were adata record form and a 5 components, 48-item questionnaire rating nurses’ caring behavior based on Swanson's Theory. The Cronbach's alpha coefficient of the overall scale was 0.96. Data analysis were frequency, percentage, mean, standard deviation, confirm factor analysis and independent t-test. The results revealed that factor analysis for a nurses’ caring behavior questionnaire by Kaiser-Meyer-Olkin Measure of Sampling Adequacy (KMO) was 0.60. Cumulative Three factors were extracted with Eigen values with more than 1.Cumulative variance was 55.18%. The factors were grouped and categorized as 1) helping with various activities, with 14 questions; 2) empowering patients to take control of their own health care, with 5 questions; and 3) maintaining the patients’ belief and faith, with 6 questions. The mean scores of nurses’ caring behaviors were at moderate levels in both groups: nurse’s group= 65.84 (SD=7.54), and patient’s group=63.35 (SD=10.37). There was a statistically significant difference between these two groups (p-value <0.05). It is suggested that these factors can be used as a basic guideline for developing of nursing practice and improving of the nurses’caring behavior.